"Another Day in Paradise": A Photovoice Journey of Rural Older Adults Living With Diabetes. (March 2015) - Yankeelov, Pamela A.; Faul, Anna C.; D'Ambrosio, Joseph G.; Collins, Wanda L.; Gordon, Barbara
This article provides the results of a photovoice project conducted with older adults affected by diabetes living in three rural counties in the southern region of the United States. Photovoice is a community-based participatory action methodology that puts the tools of research in the hands of participants. This project was an initial community engagement activity that promoted trust-building and formed part of a larger comprehensive community needs assessment. The process revealed themes of personal and community resilience focused on the daily living with diabetes, formal and informal supports, barriers to taking care of their diabetes, accessibility to fruits and vegetables, changes to food preparation and consumption, and exercise supports and barriers. The impact of the photovoice project on the participants and the implications for practice are discussed.